Structure and expression of germline epsilon transcripts in human B cells induced by interleukin 4 to switch to IgE production (The Rockefeller University Press, 1990)
Interleukin 4 (IL-4)-induced IgE production coincides with the appearance of the 2.2-kb productive epsilon-mRNA, but is preceded by synthesis of a 1.7-kb epsilon-RNA. Analysis of cDNA copies of the 5' end of this RNA indicated that the 1.7-kb epsilon-RNA is a germline epsilon immunoglobulin heavy chain transcript with an exon mapping 5' to the switch region. Transcription through switch regions has been implicated in the control of class switching. However, IL-4 or cloned CD4+ T cells were able to induce germline epsilon transcripts without inducing IgE synthesis, for which both signals were required. These results indicate that induction of human germline epsilon-RNA does not necessarily result in IgE synthesis, and that additional regulatory mechanisms are involved in class switching.